Pengaruh upah reservasi dan umur terhadap lama mencari kerja di Indonesia - Ratih Sari Dewi; Dwini Handayani (Research Centre for Population, National Research and Innovation Agency (BRIN), 2022)
Reservation wage is the main variable in the job search model. Age effect based on the life course can also explains the differences in job search behavior. This study aims to understand the effect of reservation wage and age on job search duration. Using Indonesia’s Labor Force Survey, we first estimate the reservation wage of labour force aged 15-64 years with a Two-Step Heckman regression. The results show that reservation wage and age effect have an impact on job search duration. A per cent increase in reservation wages will extend job search duration by 0.97 months. The average reservation wage of the unemployed is higher than employed with a longer job search. The study found indications of discrimination against young job seekers (15-22). They are more likely to accept any work and vulnerable to receive indecent wages and hours. The higher their education and skills, the shorter their job search duration. The study also presumes a gap in agriculture, trade, and the construction industry and informal sector, indicated by high job turnover. The synergy among the workforce, firm, and government will support the utilization of Indonesia’s demographic dividend moment.